An annotated checklist of the Collembola (Hexapoda) from Iran - Mayvan, Mahmood Mehrafrooz; Greenslade, Penelope; Sadeghi-Namaghi, Hussein (Zootaxa, 2023)
Based on available literature sources, we have listed the genera and species of springtails (Collembola) of Iran located in Southwest Asia. In total, 301 named species of Collembola are listed in catalogue. This includes 286 described species in 109 genera from 20 families recorded from Iran. Of them, 15 species are also considered as dubious species. It also includes 15 genera whose species are still unknown. Information about biology, geographical distribution, ecology, authorship records for different provinces, and bibliographical data of Iranian Collembola are included.